Preliminary clinical observation of double C-arm digital subtraction angiography guidance during transjugular intrahepatic portosystemic shunt placement - Jianqiao Chen; Xiao Bai; Chunyan Wang; Jihua Li; Weiguo Xu (BMC Gastroenterology, 2023)
Abstract Background This study aimed to investigate the safety, preliminary clinical experience, and technical advantages of double C-arm digital subtraction angiography -assisted portal vein puncture for transjugular intrahepatic portosystemic shunt. Methods Clinical data of 25 patients with portal hypertension caused by liver cirrhosis were retrospectively analyzed from January 2021 to June 2022. The fluoroscopy time, puncture time, mean portosystemic pressure gradient, dose area product, and intraoperative and postoperative complications were recorded. Results Transjugular intrahepatic portosystemic shunt was performed in all 25 patients, with a success rate of 100%. The fluoroscopy time, puncture time, and dose area product were 33.6 ± 8.5 min, 9.1 ± 5.7 min, and 126 ± 53 Gy·cm2, respectively. The mean portosystemic pressure gradient decreased from 22.5 ± 6.3 mmHg to 10.5 ± 2.3 mmHg (p < 0.01). No serious intraoperative and postoperative complications were found. Conclusion Double C-arm digital subtraction angiography-assisted portal vein puncture is safe and feasible in transjugular intrahepatic portosystemic shunt operation. It can reduce the difficulty of the operation and possesses evident technical advantages.